Mobilized Colistin Resistance (mcr) Genes, Resistotyping and Virulence Markers in Escherichia coli from Clinical and Water Samples (African Journal of Biomedical Research, 2024)
Pathogenic Escherichia coli are responsible for a diverse range of human infections and diseases, causing a significant increase in morbidity and mortality rates. This study determined the antibiotic resistance, virulence markers, and mobilized Colistin resistance genes in E. coli using the disc diffusion method and the Vitek 2 automated system, bacteriological media, and multiplex polymerase chain reaction, respectively. The results showed that 40.0%, 23.1%, and 30.0% of urine, blood, and wound samples had E. coli, while 29.4% of water samples contained E. coli. The E. coli were highly sensitive (˃ 68.4%) to Ampicillin and Ofloxacin, but ˃ 47.4% were resistant to Augmentin, Pefloxacin, and Nalidixic Acid. Of the 19 E. coli isolates, 9 (47.4%) and 8 (42.1%) exhibited intermediate resistance to Streptomycin, and Ciprofloxacin, respectively. All E. coli were resistant to Cefalexin, and 84.2% were resistant to Nalidixic Acid, while E. coli (Ec-B3) was sensitive to Ciprofloxacin. The results showed that E. coli (Ec-W1 and Ec-U5) and ExPEC (Ec-B1 and Ec-B2) shared 97.5% and 92% similarity, respectively. Of the 19 E. coli strains obtained, 69.4%, 57.9%, and 52.6% were gelatinase-, lipase-, and caseinase-producing strains, respectively. The results revealed that 57.9% of the E. coli strains were mobilized Colistin-resistant (COR), with 31.6%, 5.3%, and 21.1% having the mcr-1, mcr-2, and mcr-3 genes, respectively. The E. coli harboured some virulence markers and were highly resistant to Cefalexin, Nalidixic Acid, Augmentin, Pefloxacin, and Colistin, with mcr-1 as the predominant mcr gene. Thus, regular monitoring of antibiotic susceptibility of bacterial isolates in both the community and hospital settings is recommended